GRAM marks the spot for STIM. Commentary on "GRAM domain proteins specialize functionally distinct ER-PM contact sites in human cells". (July 2018) - Nunes, Paula; Demaurex, Nicolas
Graphical abstract: Model of GRAMD1a and GRAMD2a interactions with STIM1 and E-Syts during activation of store-operated calcium entry. Highlights: STIM1 mediates store-operated Ca 2+ entry at ER-PM membrane contact sites (MCS). GRAMD2a is a novel ER-PM tether that pre-marks the sites used by STIM1. GRAMD2a ablation impairs STIM1 translocation, but not store-operated Ca 2+ entry. We discuss these incongruent findings in the context of STIM1 signalling at MCS. Abstract: GRAM domain proteins were reported as novel ER-PM tethers defining specific membrane contact sites (MCS) subdomains. GRAMD2a pre-marks the sites occupied by STIM1 at MCS and its ablation impairs STIM1 translocation, but not store-operated Ca 2+ entry. We discuss these apparently counterintuitive findings in the context of STIM/ORAI signaling at MCS.